The Effect of Self-Control and Financial Literacy on Financial Behavior of Management Students, Faculty of Economics, Tribhuwana Tunggadewi University Malang (Survey on Management Students Class of 2021 Tribhuwana Tunggadewi University) - Mario Leonardo Jerabut; Nur Ida Iriani; Anung Prasetyo Nugroho (International Journal of Management and Business, 2025)
Many students struggle to control themselves in meeting their needs and desires. Especially in this modern era, students are sometimes easily influenced by trends, so they attach too much importance to their desires. This study aims to determine the influence of self-control and financial literacy on financial behavior among management students in the class of 2021 at Tribhuwana Tunggadewi University Malang. The research employs a quantitative approach with associative methods to measure relationships between variables. The research population consists of 229 UNITRI management students from the class of 2021, with a sample of 70 respondents determined using the Slovin formula and purposive sampling technique. Data collection was conducted through questionnaires, and data analysis used multiple linear regression with SPSS assistance. The research results show that (1) Self-control has no effect on student financial behavior, (2) Financial literacy has a significant effect on student financial behavior, and (3) Self-control and financial literacy simultaneously have a significant effect on financial behavior. This research proves that self-control and financial literacy influence student financial behavior. Students are advised to focus on developing both aspects of self-control and financial literacy to manage their finances better. Students must improve their financial literacy through education or training on budget management, investment, and long-term financial planning